Children's Interest in Learning English Through Picture Books in an EFL Context: The Effects of Parent-Child Interaction and Digital Pen Use - Naya Choi; Sujeong Kang; Jiyeon Sheo (MDPI AG, 2020)
In recent years, the ways in which to read English picture books to young children has become diverse in English as a foreign language (EFL) context. The present study examined the effect of parent-child interactions and digital pen use during English picture book reading in the child’s interest in learning English. A total of 320 Korean mothers of three to five year old preschool children participated in the study. The results revealed the following. First, children’s interest in learning English was higher when they used digital pens and engaged in frequent parent-child interactions during English picture book reading. Second, parent-child interaction was a more significant variable in children’s interest in learning English compared to digital pen use. Third, the moderator effect of digital pen use in the relation between parent-children interaction and children’s interest in learning English was insignificant. In other words, parent-child interaction was important in increasing children’s interest in learning English, regardless of digital pen use. While rapid advances in technology enhanced teaching pedagogy, parent-child interaction in foreign language learning still remains as a crucial factor. Further implications and future directions are discussed.